Prosthetic failures in dental implant therapy. Issue 1 (1st February 2022) - Sailer, Irena; Karasan, Duygu; Todorovic, Ana; Ligoutsikou, Maria; Pjetursson, Bjarni Elvar
Abstract: Both fixed and removable implant‐supported prostheses are well‐established methods for replacing missing teeth in partially or fully edentulous patients. Numerous systematic reviews have been performed in recent years to evaluate the survival and complication rates of implant‐retained fixed dental prostheses and implant‐retained overdentures, displaying high 5‐year survival rates ranging from 97.1% for fixed dental prostheses to 95%‐100% for implant‐retained overdentures. However, the survival rates only represent the prostheses remaining in use for a defined follow‐up time, and do not account for the potential prosthetic complications that may have arisen and influence the general success of the implant treatment. The most common technical complications of fixed implant‐retained single crowns are crown fracture, fractures of ceramic implant abutments, and esthetic problems. The predominant technical complication at multiple‐unit, implant‐retained fixed dental prostheses is fracture/chipping of the veneering ceramic. Reported technical complications for implant‐retained overdentures are overdenture fracture or chipping of the veneer materials, whereas mechanical complications include implant fracture, attachment failure, and attachment housing or insert complications. To reduce the risk of such failures, a comprehensive pretreatment diagnostic work‐up is essential, including defining the prosthetic goal with the aid of a wax‐up or set‐up and the associated ideal, prosthetically oriented three‐dimensional implant position. Furthermore, selection of the ideal type of prosthesis, including the respective implant components and materials, is important for clinical long‐term treatment success.